DIVELOPING INTERACTIVE CD BY USING PICTURE AND PICTURE METHOD IN TEACHING TIK (INTERNET SUB TOPIC) AT GRADE NINE OF SMPN 1 BANJAR IN ACADEMIC YEAR 2012/2013 - Ambara Wijaya, I Gede (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This research aimed at (1) designing learning media, interactive CD by using picture and picture method to be used to teach about internet in SMPN 1 Banjar at grade nine, (2) implementing interactive CD by using picture and picture method to be used to teach about internet in SMPN 1 Banjar at grade nine, and (3) describing the responses from the ninth grade students and the computer teacher about the interactive CD that was designed to teach internet subtopic. The kind of this research was R&D (Research and Development) which the development models implemented were Dick and Care model and waterfall model. The subject of this research was the ninth grade students of SMPN 1 Banjar in academic year 2012/2013. The number of the students that were participated in this research was 10 students from IX A class.  To acquire the aim above, several instruments were used in collecting data, such as interview guide and checklist. Interview was conducted to know the problems faced by the teacher in teaching about internet in grade nine. Meanwhile, the checklist was used to collect the data from teacher and students about the media that was designed.    The result of this research was seen from the students and teacher checklists which shows that  the distributions of the students and teacher weres 100% positive. Further, the responses from the computer teacher and the students show that the interactive CD is interesting and suitable to be used to teach internet subtopic for the ninth grade students of SMPN 1 Banjar.